Isolation and Characterization of Mold on Furniture in Biological Laboratory Environment Using Contact Plate Method - Wahyu Aji Mahardhika; Romario Dion; Mochammad Fa’iq Qoys Naufal; Warih Ramadhany; Arina Tri Lunggani (Jurnal Biologi Tropis, 2022)
The presence of molds in the environment around us can be beneficial or detrimental. Mold can be found in various places, including soil, air, plants, animals, water, and on material surfaces. One of the roles of mold is as a bio-degradator and biodeterioration agent on materials that are still used, so that it will cause harm to humans. This study aims to isolate and characterize the types of molds that exist on the surface of existing materials in the biology laboratory environment of Diponegoro University with the contact plate method. The method used is to attach a contact plate containing PDA to various materials such as tables, chairs, cabinets, and so on, then observe the macroscopic and microscopic morphology. The results obtained were five genera, there are Aspergillus, Penicillium, Eurotium, Rhizopus, and Absidia.